Circannual rhythms and interactions of vitamin D metabolites, parathyroid hormone, and biochemical markers of skeletal homeostasis: a prospective study - Woitge, Henning W.; Knothe, Antje; Witte, Klaus; Schmidt-Gayk, Heinrich; Ziegler, Reinhard; Lemmer, Björn; Seibel, Markus J. (Journal of bone and mineral research, 2000)
Recent studies suggest a circannual pattern of bone turnover. To further investigate the underlying mechanisms, 41 healthy subjects (25-80 years old) living in a southwestern German city were studied prospectively over a period of 18 months. Participants were examined every 4 weeks, and blood and urine samples were obtained on each visit. The following parameters were measured: serum 25-hydroxyvitamin D3 [25(OH)D3], 1,25-dihydroxyvitamin D3 [1,25(OH)2D3], and parathyroid hormone (PTH), as regulators, and serum total alkaline phosphatase (TAP), bone-specific alkaline phosphatase (BAP), urinary total pyridinoline (PYD), deoxypyridinoline (DPD), and the aminoterminal telopeptide of collagen type I (NTX), as biochemical markers of bone turnover. The presence of significant circannual rhythms for the various markers was tested using the Pharmfit method. In the total group, 25(OH)D3, 1,25(OH)2D3, and PTH as well as BAP, PYD, DPD, and NTX showed a significant seasonal variation. 25(OH)D3 revealed the highest amplitude (38.0%) with an acrophase in August. Levels of the biochemical markers and of PTH were highest in winter with amplitudes of up to 17.7% (DPD). Results were most pronounced in premenopausal women, in subjects <50 years of age, and in subjects who did show a significant individual rhythm in 25(OH)D3 levels. No differences were found regarding other anthropometric or life style factors. Correlation analyses revealed strongest associations between the amplitudes of a vitamin D metabolite and a biochemical marker in premenopausal women. We conclude that specific markers of bone turnover show significant circannual rhythms. These changes are related directly to variations in the hormonal regulation of skeletal homeostasis. In postmenopausal women and in men, other effects may superimpose the circannual variation of biomarkers of bone turnover.